2004
DOI: 10.1111/1469-8986.2004.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral blood flow correlates with heart period and high‐frequency heart period variability during working‐memory tasks: Implications for the cortical and subcortical regulation of cardiac autonomic activity

Abstract: The aim of the present study was to characterize the functional relationships between behaviorally evoked regional brain activation and cardiac autonomic activity in humans. Concurrent estimates of regional cerebral blood flow (rCBF; obtained by positron emission tomography), heart period, and high-frequency heart period variability (HFHPV; an indicator of cardiac parasympathetic activity) were examined in 93 adults (aged 50-70 years) who performed a series of increasingly difficult working-memory tasks. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
226
4
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(254 citation statements)
references
References 40 publications
22
226
4
2
Order By: Relevance
“…The cerebellum is certainly involved in physiological regulation as a component of the central autonomic network (Spyer, 1999) contributing to the control of cardiovascular responses through its connections with the hypothalamus (Critchley, Corfield, Chandler, Mathias, & Dolan, 2000). Accordingly, covariation is observed between HRV and the cerebellum (Critchley et al 2003;Gianaros, Van Der Veen, & Jennings, 2004;Lane et al, 2009;Napadow et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellum is certainly involved in physiological regulation as a component of the central autonomic network (Spyer, 1999) contributing to the control of cardiovascular responses through its connections with the hypothalamus (Critchley, Corfield, Chandler, Mathias, & Dolan, 2000). Accordingly, covariation is observed between HRV and the cerebellum (Critchley et al 2003;Gianaros, Van Der Veen, & Jennings, 2004;Lane et al, 2009;Napadow et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Gianaros et al covaried HF with H 2 15 O PET during graded memory tasks (Gianaros et al 2004) and found that regional cerebral blood flow (rCBF) covaried positively with HF in the right VMPFC, left insula, and left amygdala-hippocampal complex, while covarying negatively in the right cerebellum. Lane et al similarly covaried HF with PET neuroimaging during an emotion-laden task (Lane et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have attempted to relate estimates of efferent autonomic activity using HF power with concurrent brain response using Positron Emission Tomography (PET) (Lane et al 2001;Gianaros et al 2004) or functional Magnetic Resonance Imaging (fMRI) (Critchley et al 2003;Napadow et al 2005) during behavioral tasks that are thought to modulate the ANS. Correlating fMRI task response with out-of-scanner baseline HF (O'Connor et al 2007) or HF response to the in-scanner task (Matthews et al 2004) has also been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Sympathetic activity, as measured by pupillary dilation (Critchley et al, 2005) and skin conductance responses (Nagai et al, 2004), have both been correlated with neural activation in the anterior cingulate cortex (ACC). Parasympathetic activity, as measured by the highfrequency component of heart rate variability, has also been associated with the ACC during fMRI tasks involving working memory and emotion (Gianaros et al, 2004;Lane et al, 2001;Matthews et al, 2004). The demonstrated relationship between autonomic activity indicative of arousal and ACC activity is consistent with the dense projections from the ACC to cell groups that regulate autonomic functions, such as the amygdala, hypothalamus, and brainstem nuclei (Neafsey et al, 1993).…”
Section: Introductionmentioning
confidence: 87%